Enhancing Ruminant Fermentation with Bioethanol-Waste-Derived Yeast: In Vitro Evaluation of Digestibility, Gas Production, and NH? Concentration - Nurzaky, Khoiri; Marjuki; Pamungkas, Dicky (Faculty of Animal Science, Universitas Brawijaya, 2025)
This study analyzed the effect of yeast extracted from bioethanol waste as a direct-fed microorganism for ruminant livestock. Testing was conducted in vitro to assess the effect of yeast on ruminant livestock through dry matter and organic matter digestibility, gas production, and NH3 concentration. This study was divided into two phases. The first phase of research involved yeast cell cultivation and yeast powder production. The second research phase is an in vitro digestibility, gas production, and NH3 concentration analysis. The results of the first research phase were intended to obtain yeast samples that were cultivated using inoculum from purified bioethanol waste, which would be used for testing materials in the second research phase. The results of cell viability in processed yeast were 37.79%. The results of the second research phase showed that adding yeast as a feed additive to complete feed significantly increased the value of dry matter digestibility, organic matter digestibility, gas production, and NH3 concentration. The results of the in vitro study showed the highest dry matter digestibility (DMD) and organic matter digestibility (OMD) in the T3, which were 66.09% and 66.99%; the gas production results also showed the highest value in the T3 for total gas production 48h (161.15 ml/500 mg DM), gas production potential (171.24 ml/500 mg DM), and gas production rate (0.057 ml/hour). The T3 treatment also showed the highest NH3 concentration of 10.80 mM. The overall results of the research phases showed good results related to the use of yeast as an additive in complete feed, and the addition of 2% yeast gave the most significant results on the in vitro digestibility, gas production, and NH3 concentration.